Pengaruh Youtube Advertising terhadap Brand Awareness dan Purchase Intention - Yunita, Dessy; Nazaruddin, Ahmad; Nailis, Welly (University of Merdeka Malang, 2019)
This study aims to examine the influence of YouTube Advertising on brand awareness and purchase intention. This study uses a conclusive design with single cross sectional. The number of samples are 210 respondents who watched advertisements on Youtube as research objects. Entertainment, informativeness, irritation, credibility, brand awareness and purchase intention are used to discuss the results of research. The results of this study show that the Youtube Advertising dimension does not influencee brand awareness, but brand awareness has impact on purchase intention.https://doi.org/10.26905/jmdk.v7i1.2538